Inflationary Rate and Investment in Nigeria - Adu, Cecilia Adurayemi; Ajigbotoso, Moses Ade (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study determined the effect of inflationary rate on investment in Nigeria. The descriptive method was used. It was noted that structural rigidities and ineffectual policy recommendations exacerbated the negative effects of inflation on Nigeria's financial sector. It was recommended that the nation enact laws that would expedite sustainable development by requiring significant investment, and that the state guarantee the availability of facilities that would support and stimulate significant investment.